Exploring the Preventive Potential of Solubilized Sturgeon Oil on Acute Infection with Respiratory Viruses - Seong Ok Park; Erdenebileg Uyangaa; Yong-Kwang Lee; Suk-Hyun Yun; Minyeong Yu; Hyo Jin Kim; Hye Won Cho; Hee Won Byeon; Chong-Kil Lee; Seong Kug Eo (Marine Drugs)
Acute respiratory viral infections (ARIs) represent a significant global health challenge, contributing heavily to worldwide morbidity and mortality rates. Recent efforts to combat ARIs have focused on developing nasal spray formulations that effectively target the nasal mucosa. However, challenges such as irritation, discomfort, and safety concerns highlight the need for natural, eco-friendly ingredients. In this study, we evaluated the efficacy of solubilized sturgeon oil (SSO), prepared as an oil-in-water nanoemulsion from Siberian sturgeon, as an eco-friendly preventive nasal spray agent against ARIs. Intranasal pre-treatment with SSO effectively inhibited respiratory infections caused by SARS-CoV-2, influenza A virus (IAV), and respiratory syncytial virus (RSV). Additionally, it suppressed viral replication in both nasal and lung tissues. This antiviral effect was linked to reduced pulmonary inflammation, characterized by decreased infiltration of Ly-6C+ monocytes and Ly-6G+ neutrophils, along with lower pro-inflammatory cytokine levels. Histopathological analyses confirmed that nasal SSO administration significantly mitigated lung inflammation progression caused by viral infections. Notably, the protective effects of SSO against SARS-CoV-2, IAV, and RSV persisted for at least six hours following nasal application. These findings highlight SSO as a promising eco-friendly and safe candidate for nasal spray formulations, providing a potential frontline defense against ARIs.